The imperial network in ancient China: the foundation of Sinitic empire in southern East Asia - Korolkov, Maxim (RoutledgeCurzon studies in the early history of Asia, 2022)
List of illustrations -- Historical periods -- Acknowledgments -- Chapter 1. Introduction -- Chapter 2. Before the empire: the middle Yangzi interaction space -- Chapter 3. Qin's southward expansion -- Chapter 4. The Qin empire in the south: territoriality, organization, challenges -- Chapter 5. Local administration in the south -- Chapter 6. Resources and resource exploitation -- Chapter 7. Southern borderlands after the Qin -- Epilogue: Networks, empires, world-systems: southern East Asia and the dynamics of early Sinitic empire -- Appendix 1. Origins of individuals in Qianling County -- Appendix 2. Grain ration records in Qianling County -- Appendix 3. Increase in the registered population of the southern commanderies between 2 CE and 156 CE -- Glossary of Chinese terms -- Bibliography.
Includes bibliographical references and index
Die Bandzählung sollte lauten: 13
Keywords: China, Southeast -- Politics and government; China, Southeast -- History; China -- Territorial expansion -- History; China -- Politics and government -- 221 B.C.-220 A.D; China -- History -- 221 B.C.-960 A.D; China -- History -- Qin dynasty, 221-207 B.C; Asia; China; Geschichte 400 v. Chr.-200; Expansionspolitik; Kaiserreich; Feudalismus